The role of human Metapneumovirus genetic diversity and nasopharyngeal viral load on symptom severity in adults - Oong, Xiang Yong; Chook, Jack Bee *; Ng, Kim Tien; Chow, Wei Zhen; Chan, Kok Gan; Hanafi, Nik Sherina; Pang, Yong Kek; Chan, Yoke Fun; Adeeba Kamarulzaman,; Tee, Kok Keng (BioMed Central, 2018)
Background:Human metapneumovirus (HMPV) is established as one of the causative agents of respiratory tract infections. To date, there are limited reports that describe the effect of HMPV genotypes and/or viral load on disease pathogenesis in adults. This study aims to determine the role of HMPV genetic diversity and nasopharyngeal viral load on symptom severity in outpatient adults with acute respiratory tract infections. Methods: Severity of common cold symptoms of patients from a teaching hospital was assessed by a four-category scale and summed to obtain the total symptom severity score (TSSS). Association between the fusion and glycoprotein genes diversity, viral load (quantified using an improved RT-qPCR assay), and symptom severity were analyzed using bivariate and linear regression analyses. Results: Among 81/3706 HMPV-positive patients, there were no significant differences in terms of demographics, number of days elapsed between symptom onset and clinic visit, respiratory symptoms manifestation and severity between different HMPV genotypes/sub-lineages. Surprisingly, elderly patients (≥65 years old) had lower severity of symptoms (indicated by TSSS) than young and middle age adults (p = 0.008). Nasopharyngeal viral load did not correlate with nor predict symptom severity of HMPV infection. Interestingly, at 3–5 days after symptom onset, genotype A-infected patients had higher viral load compared to genotype B (4.4 vs. 3.3 log10 RNA copies/μl) (p = 0.003). Conclusions: Overall, HMPV genetic diversity and viral load did not impact symptom severity in adults with acute respiratory tract infections. Differences in viral load dynamics over time between genotypes may have important implications on viral transmission.